1994
DOI: 10.1038/369533a0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of megakaryocytopoiesis and thrombopoiesis by the c-Mpl ligand

Abstract: Physiological platelet synthesis is thought to require the humoral activities of meg-CSF and thrombopoietin, which respectively promote proliferation and maturation of megakaryocytic cells. A meg-CSF/thrombopoietin-like protein that is present in plasma of irradiated pigs has been purified and cloned. This protein binds to and activates the c-mpl protein, a member of the cytokine receptor superfamily. The isolated Mpl ligand shares homology with erythropoietin and stimulates both megakaryocytopoiesis and throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
725
0
5

Year Published

1995
1995
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,293 publications
(746 citation statements)
references
References 40 publications
13
725
0
5
Order By: Relevance
“…14,16 However, the CFU-MK assay has yielded variable results, in part, because best growth is obtained with a combination of growth stimulators, colony size can be quite small, and colony identification can present problems to the inexperienced observer. 25 In the present study, we used TPO and SCF as growth factors for CFU-MK; these produce more and larger colonies than previous methods, [18][19][20][21] and these CFU-MK characteristics were inversely correlated with the time to platelet recovery (r = Ϫ0.55). Although colony assays are reliable with TPO, the method is laborious and requires 2 weeks to obtain results, making it generally unsuitable for use as a routine method in a clinical laboratory.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…14,16 However, the CFU-MK assay has yielded variable results, in part, because best growth is obtained with a combination of growth stimulators, colony size can be quite small, and colony identification can present problems to the inexperienced observer. 25 In the present study, we used TPO and SCF as growth factors for CFU-MK; these produce more and larger colonies than previous methods, [18][19][20][21] and these CFU-MK characteristics were inversely correlated with the time to platelet recovery (r = Ϫ0.55). Although colony assays are reliable with TPO, the method is laborious and requires 2 weeks to obtain results, making it generally unsuitable for use as a routine method in a clinical laboratory.…”
Section: Discussionmentioning
confidence: 89%
“…13,14,16,17 Thrombopoietin (TPO), the ligand for the c-mpl receptor, has been shown to stimulate the growth of megakaryocyte colonies in vitro. [18][19][20] The number and size of CFU-MK induced by TPO was greater than that induced by any other combination of growth factors, suggesting that TPO may be useful for assaying CFU-MK. 21 Based on these observations, we analyzed the expression of different platelet glycoproteins on CD34 + cells by flow cytometry and the number of TPO-induced CFU-MK in PBSC grafts.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several groups [2][3][4][5] cloned the ligand for the c-Mpl proto-oncogene [6] which is a member of the cytokine receptor superfamily. These studies and others have demonstrated that c-Mpl ligand plays a critical role in megakaryocytopoiesis and thrombopoiesis both in vitro and in vivo [2][3][4][5][7][8][9][10]. Therefore, c-Mpl ligand has been termed thrombopoietin (TPO) [3,7,8] or megakaryocyte growth and development factor (MGDF) [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The recently defined ligand for the Mpl receptor, thrombopoietin (TPO), has been found to be the principal regulatory cytokine of megakaryocytopoiesis and thrombopoiesis. [4][5][6][7][8] It appears that TPO is able not only to induce differentiation of megakaryocytic precursors, but also to expand early megakaryocytic progenitors. 9,10 TPO also directly affects more primitive hematopoietic cells, not yet committed towards the megakaryocytic lineage.…”
Section: Introductionmentioning
confidence: 99%